2019
DOI: 10.1016/j.jds.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of upper airway measurement by lateral cephalogram in upright position and CBCT in supine position

Abstract: Background/Purpose Obstructive sleep apnea syndrome (OSAS) is a common form of sleep disorder. Lateral cephalograms and cone-beam computed tomography (CBCT) have been used for evaluation. However, it is lack of position comparison for these two assessments. Therefore, this study was aimed to evaluate the difference of upper airway measurements taken from lateral cephalograms in upright position and CBCT in supine position. Material and methods This retrospective study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
(37 reference statements)
0
16
0
1
Order By: Relevance
“…In fact, Pcrit and pharyngeal dilator muscle activity (which is equivalent to Eckert et al's "UA collapsibility" and "muscle responsiveness") are sleep-stage dependent (37). Predictability of H-MP for OSA severity are high (1,2) and is greater than those of minimal posterior airway space (PAS) measurements as has been previously reported (38). As reported by Wheatley et al (8) and this study, the average amount the hyoid bone elevation by AMP use is ∼5 mm.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In fact, Pcrit and pharyngeal dilator muscle activity (which is equivalent to Eckert et al's "UA collapsibility" and "muscle responsiveness") are sleep-stage dependent (37). Predictability of H-MP for OSA severity are high (1,2) and is greater than those of minimal posterior airway space (PAS) measurements as has been previously reported (38). As reported by Wheatley et al (8) and this study, the average amount the hyoid bone elevation by AMP use is ∼5 mm.…”
Section: Discussionmentioning
confidence: 67%
“…The hyoid bone moves superiorly in the supine position in asymptomatic subjects, while the tongue mass sinks by 30% due to gravitational pull, as the oropharyngeal space is reduced by 30% (6,38). In the supine body position, tongue and suprahyoid electromyogram (EMG) activity (principally the genioglossus) increases by 30%.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al [ 17 ] further found that the minimum of PAS and linear distance along perpendicular changes from the most upper anterior point of the hyoid bone to mandibular plane, as the position of body is changed from upright to supine[ 17 ]. Nevertheless, in recent times, advancements in CBCT have permitted axial CT images to be acquired in upright sitting posture, which is more valid for our study.…”
Section: Discussionmentioning
confidence: 99%
“…In our study CBCT was done in upright position for the evaluation of OSAHS. A study conducted by Wun Eng Hsu et al 23 to evaluate the change in upper airway measurements comparing lateral cephalogram in upright position and CBCT in supine position suggested that, mean anterior-posterior distance in the oropharynx and mandibular plane to hyoid bone distance can be influenced by the change in the body posture 23 .…”
Section: Discussionmentioning
confidence: 99%